Analysis of Factors Affecting the Amount of Credit Distribution at Credit Unions - Anggrella Simbolon (Institute of Computer Science (IOCS), 2021)
Capital is the most important thing in production activities. Without capital, it is impossible for a production activity to run as it should. Likewise for entrepreneurs, especially micro, small and medium entrepreneurs who generally experience problems in terms of capital. These capital giving institutions are generally handled by the banking sector. However, for various reasons, these micro, small and medium entrepreneurs rely more on credit originating from non-governmental organizations which are currently emerging in the community. The institution emerged to develop a small credit mechanism specifically for micro, small and medium entrepreneurs. Like the Credit Union, it is one of the credit providers for micro, small and medium entrepreneurs.